Plant Rhizodeposition and Rhizosphere Microflora: Their Relationship and Its Consequences in Wetlands - Kubešová, Jaroslava (Jihočeská univerzita, 2010)
Annotation: Plant and microbial relationships in the rhizosphere have been briefly reviewed. The research of tropical wetland ecosystem in northern Belize has been summarized. After that a synthesis of both parts results in the hypothesis of carbon, nitrogen and phosphorus flows between Eleocharis cellulosa, Typha domingensis and their rhizosphere.
Plant Rhizodeposition and Rhizosphere Microflora: Their Relationship and Its Consequences in Wetlands
Keywords: rhizosphere; rhizodeposition; root; wetland; microbial; nitrogen; phosphorus; carbon; Typha; Eleocharis